Human Health Effects Associated With The Commercial Use Of Grunerite Asbestos (Amosite): Paterson, NJ; Tyler, TX; Uxbridge, UK - Joseph Ribak (Society for Mining, Metallurgy & Exploration, 2007)
Grunerite asbestos (amosite) has been shown in epidemiological and experimental animal studies to cause lung cancer, mesothelioma and pulmonary fibrosis commonly referred to as asbestosis. An overview of the human and experimental animal studies describing the health hazards of grunerite asbestos (amosite) is presented. Of the many human studies describing the health hazards of asbestos, only three factories using mainly, if not exclusively, grunerite asbestos (amosite) have been studied. The first is a series of reports on a cohort of 820 workers from a plant located in Paterson, NJ. Among this cohort, 18.7% died of lung cancer and 17 mesotheliomas occurred. The Paterson factory closed in 1954 and moved to Tyler, Texas where it operated until 1972. Among the 1130 former workers in the Tyler plant 6 mesotheliomas were reported with 15.8% lung cancer mortality. The third grunerite asbestos (amosite) exposed cohort was an insulation board manufacturing facility in Uxbridge, United Kingdom. Here 17.1% of the workers died of lung cancer and 5 mesotheliomas occurred. The lung content from 48 Uxbridge workers was analyzed by analytical transmission electron microscopy for mineral fibers. The relationship between grunerite asbestos (amosite) concentrations in the lung correlated with grades of fibrosis and asbestos bodies and was lower than the concentration found in the cases with malignant tumors. The lung cancer cases contained more grunerite asbestos (amosite) than mesothelioma cases, and in the cases of non-alignant disease the concentrations were still lower. In both types of malignancies the concentration of grunerite asbestos (amosite) was very high-over a billion fibers per gram of dried lung tissue. Occupational exposure to airborne concentrations of between 14 and 100 fibers of grunerite asbestos (amosite) per milliliter after 20 year latency causes marked increases in lung cancer, mesothelioma and pulmonary fibrosis (asbestosis). © 2007 Elsevier Inc. All rights reserved. Keywords: Grunerite asbestos; Amosite; Mesothelioma; Asbestosis